Development of Chronic Kidney Disease Screening Integrative Care Model Led by Community Pharmacists - Piangkwan Srimongkhol; Sirirat Anutrakulchai; Amponpun Theeranut; Nonglak Methakanjanasak; Sunee Lertsinudom (Pharmacy)
Background: The prevalence of chronic kidney disease (CKD) is rising, increasing demand for renal replacement therapy (RRT). Community pharmacies, as accessible healthcare hubs, can play a pivotal role in CKD prevention. This study aimed to develop care models for community pharmacies to optimize medication use, encourage behavior modification, and promote self-management among at-risk individuals. Methods: Conducted between June 2017 and July 2018, this study utilized an action research approach. Microalbuminuria was assessed using urine dipsticks, and pharmacists applied behavioral change and self-management support (SMS) strategies to slow CKD progression. Participants were categorized by albuminuria levels and enrolled in pharmacist-led care programs, with follow-up assessments at weeks 0 and 12. Results: Of 521 participants screened, 57% tested positive for albuminuria. For these individuals, serum creatinine testing and referrals to primary care were initiated. Self-management behavior assessment (S1) scores significantly improved (p = 0.024). Key factors associated with urine albumin levels included age < 60 years (OR = 0.44), diabetes (OR = 3.69), hypertension (OR = 2.01), BMI < 27.5 kg/m2 (OR = 0.42), eGFR ≥ 60 mL/min/1.73 m2 (OR = 3.34), lower systolic (OR = 0.55) and diastolic blood pressure (OR = 0.34), and fasting plasma glucose < 126 mg/dL (OR = 0.29). Conclusions: Community pharmacist-led albuminuria screening effectively supports CKD prevention and enhances self-awareness within communities.